The Effect of Profitability, Liquidity, and Company Size on Stock Prices - Amellia Putri Setianingrum; Anisaul Hasanah; Firdaus Indrajaya Tuharea (Brilliant International Journal Of Management And Tourism, 2025)
This study investigates the influence of profitability, liquidity, and company size on stock prices among technology companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The research addresses the question of whether traditional financial indicators remain valid in explaining stock price variations in high growth and volatile sectors such as technology, particularly during the post-pandemic period. Using a purposive sampling method, the study selects 10 technology firms as the sample, with data obtained from annual financial statements and processed using SPSS version 26. Multiple linear regression is employed alongside classical assumption tests to assess both the partial and simultaneous effects of the variables. The results reveal that profitability, as measured by Return on Equity (ROE), has a significant and positive effect on stock prices, highlighting its reliability as a performance signal to investors. In contrast, liquidity and company size do not show a statistically significant positive influence, suggesting that these traditional metrics may be less effective in assessing stock performance in dynamic technology markets. The findings underscore the need for investors to prioritize profitability when evaluating technology stocks and prompt companies to strengthen their financial performance to enhance market valuation. This study contributes to the literature by offering empirical evidence specific to Indonesia’s digital economy and by providing practical implications for investment decision making in emerging markets.